2021
DOI: 10.3390/foods10122998
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Homogenization and Biocontrol Agent as Innovative Approaches Increase Shelf Life and Functionality of Carrot Juice

Abstract: Recently, application of high-pressure homogenization (HPH) treatments has been widely studied to improve shelf life and rheological and functional properties of vegetable and fruit juices. Another approach that has drawn the attention of researchers is the use of biocontrol cultures. Nevertheless, no data on their possible combined effect on fruit juices shelf life and functionality have been published yet. In this work, the microbial, organoleptic, and technological stability of extremely perishable carrot j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
2
5
0
1
Order By: Relevance
“…The total mesophilic bacteria count for pure carrot juice observed at the time of preparation puts it in the usual range of TMB count for fresh carrot juice [38][39][40]. Ben-Fadhel et al [41] have noted a decrease of almost two logarithmic cycles in the TMB count in fresh carrots after treatment with antimicrobial formulation (mixture of EOs), which is similar to the result obtained in this work.…”
Section: Microbiome Analysessupporting
confidence: 88%
See 1 more Smart Citation
“…The total mesophilic bacteria count for pure carrot juice observed at the time of preparation puts it in the usual range of TMB count for fresh carrot juice [38][39][40]. Ben-Fadhel et al [41] have noted a decrease of almost two logarithmic cycles in the TMB count in fresh carrots after treatment with antimicrobial formulation (mixture of EOs), which is similar to the result obtained in this work.…”
Section: Microbiome Analysessupporting
confidence: 88%
“…The total mesophilic bacteria count in all juice variants increased noticeably after 4 days of storage, and microbial spoilage appeared to be even across all variants. Interestingly, Gottardi et al [38] also did not observe a significant change in the microbial quality of fresh carrot juice during 48 h of storage-in fact, the TMB count of pure carrot juice observed after 2 days of storage was lower than the initial one; however, the TMB of their juice had exceeded 7.0 log CFU/mL after 9 days of storage, which generally indicates the state of microbial spoilage in fresh produce or its direct derivatives. Interestingly, Leneveu-Jenvrin et al [42] observed that commercial carrot juice presented much better microbial quality by TPB count than TMB count, as, even after three days of storage, it did not exceed 5.0 log CFU/mL.…”
Section: Microbiome Analysesmentioning
confidence: 95%
“…In the process of biodiesel production more than 90% of the operating cost comes from raw materials, of which almost 78% of the cost comes from feedstocks (Naveenkumar and Baskar, 2021). For this reason, several investigations to find a low-cost alternative feedstock for SCO production have been conducted (Papanikolaou and Aggelis, 2002;Papanikolaou et al, 2003;Tchakouteu et al, 2015;Sarris et al, 2017;Gottardi et al, 2021). Macroalgae are common in water ecosystems and, notably, they can grow at rates that far exceed those of terrestrial plants (Takagi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte en la evaluación de inactivación enzimática y microbiológica, color y propiedades sensoriales post procesamiento en jugo de fresa, se obtuvo como resultados la mejora de la vida útil de la bebida de fresa otorgándole un tiempo de 49 días cuando estas fueron procesadas a 500 o 600 MPa, no hubo cambios significativos en el contenido de antocianinas y vitamina C por lo que no se observaron cambios de color después del procesamiento [7]. Asimismo, en la evaluación de la funcionabilidad del jugo de zanahoria así como su estabilidad microbiana y organoléptica, se logró que a 150MPa prolongó la vida útil del producto de 3 a 7 días almacenados a temperaturas de 10 a 4 °C; además, otorgó una mayor estabilidad en los valores de color y pH [8].…”
Section: Introductionunclassified